2000
DOI: 10.1037/0022-3514.79.3.452
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural evidence for the fundamental features of extraversion.

Abstract: Psychologists have not determined the defining characteristics of extroversion. In four studies, the authors tested the hypothesis that extraversion facets are linked by reward sensitivity. According to this hypothesis, only facets that reflect reward sensitivity should load on a higher order extraversion factor. This model was tested against a model in which sociability links fee facets. IDS authors also tested the generalizability of the model in a diverse sample of participants from 39 nations, and they tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
428
5
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 619 publications
(472 citation statements)
references
References 37 publications
26
428
5
7
Order By: Relevance
“…Eysenck & Eysenck, 1985;Furnham & Heaven, 1999). Furthermore, this finding is in accord with evidence that the core feature of Extraversion is reward sensitivity, rather than sociability (Lucas, Diener, Grob, Suh, & Shao, 2000). In contrast to the strong negative correlations between all seven primary scales of Stability and the hygiene composite reported by , in the present study, Stability correlated (positively) with the motivator, but not with the hygiene composite.…”
Section: Discussioncontrasting
confidence: 57%
“…Eysenck & Eysenck, 1985;Furnham & Heaven, 1999). Furthermore, this finding is in accord with evidence that the core feature of Extraversion is reward sensitivity, rather than sociability (Lucas, Diener, Grob, Suh, & Shao, 2000). In contrast to the strong negative correlations between all seven primary scales of Stability and the hygiene composite reported by , in the present study, Stability correlated (positively) with the motivator, but not with the hygiene composite.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous research has found that affiliation, warmth, and trustworthiness are strongly correlated with each other, and all of them relate to the dimension of valence (Lucas, Diener, Grob, Suh, & Shao, 2000;. This fits well with the results of the current study, in which the results for these three traits were highly consistent.…”
Section: Discussionsupporting
confidence: 82%
“…The trait aspect of SWB, in contrast, is more stable and varies less strongly (i.e., in longer cycles) and at a smaller amplitude around the individual set point. In addition, trait SWB is determined to a greater extent by stable personality characteristics (e.g., extraversion, see [34]) and reveals a markedly higher temporal and situational consistency. Although these two aspects are differentiated clearly on a theoretical level, there are no concrete indications regarding how far one can talk about a "right now" (or state) SWB and specify when this changes into a "longer time period" (or trait) SWB.…”
Section: Dynamic Aspects Of Swbmentioning
confidence: 99%